2014
DOI: 10.1371/journal.pone.0096895
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Vitreous Humor of Patients with Exudative Age-Related Macular Degeneration

Abstract: BackgroundThere is absence of specific biomarkers and an incomplete understanding of the pathophysiology of exudative age-related macular degeneration (AMD).Methods and FindingsEighty-eight vitreous samples (73 from patients with treatment naïve AMD and 15 control samples from patients with idiopathic floaters) were analyzed with capillary electrophoresis coupled to mass spectrometry in this retrospective case series to define potential candidate protein markers of AMD. Nineteen proteins were found to be upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 38 publications
(45 reference statements)
4
74
1
Order By: Relevance
“…Mass spectrometry (MS)‐based quantitative proteomics provides a means for the determination of global proteome changes at the tissue and cellular levels, enabling a molecular level characterization of the pathophysiologies of complex eye disorders. Currently, most proteomic studies characterizing disease‐induced vitreous proteome changes have focused on proliferative and nonproliferative diabetic retinopathies (Kim et al, 2007; Loukovaara et al, 2015; Wang, Feng, Hu, Xie, & Wang, 2013), proliferative vitreoretinopathy (Garweg, Tappeneiner, & Halberstadt, 2013; Mitry, Fleck, Wright, Campbell, & Charteris, 2010), and age‐related macular degeneration (AMD; Koss et al, 2014), whereas iERM and MH remain less‐studied (Mandal et al, 2013; Pollreisz et al, 2013; Yu et al, 2014; Zhang et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry (MS)‐based quantitative proteomics provides a means for the determination of global proteome changes at the tissue and cellular levels, enabling a molecular level characterization of the pathophysiologies of complex eye disorders. Currently, most proteomic studies characterizing disease‐induced vitreous proteome changes have focused on proliferative and nonproliferative diabetic retinopathies (Kim et al, 2007; Loukovaara et al, 2015; Wang, Feng, Hu, Xie, & Wang, 2013), proliferative vitreoretinopathy (Garweg, Tappeneiner, & Halberstadt, 2013; Mitry, Fleck, Wright, Campbell, & Charteris, 2010), and age‐related macular degeneration (AMD; Koss et al, 2014), whereas iERM and MH remain less‐studied (Mandal et al, 2013; Pollreisz et al, 2013; Yu et al, 2014; Zhang et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Cataract is one of the most prevalent eye diseases, and numerous studies have been conducted to investigate the underlying mechanisms of cataract development for potential prevention and treatment strategies [1][2][3][4]. Many evidences have showed that age is the biggest risk factor [5].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics studies proteins at a large scale, and has been used in AMD research to study the protein content of drusen, macular, retinal, and RPE components, plasma, and eye fluids. [104][105][106][107][108][109][110][111] Epigenomics studies the methylation state of our DNA, which correlates to altered gene expression levels. These methylation patterns can be altered by our lifestyle, for example by smoking or by our diet.…”
Section: Omics In Amd Researchmentioning
confidence: 99%